P–728 Can in couples with unexplained infertility the use of a prediction model to triage assisted reproduction technology save costs?. (6th August 2021) - Nguyen, D K; OLeary, S; Gadalla, M A; Wang, R; Li, W; Song, Z; Roberts, B; Alvino, H; Tremellen, K P; Mol, B W
Abstract: Study question: Can in couples with unexplained infertility a prognosis-tailored management strategy, that delays treatment if natural conception prospects are good, reduce costs without affecting live-birth rate? Summary answer: In couples with unexplained infertility, use of a prognostic tool for natural conception followed by expectant management in good-prognosis couples is cost-effective. What is known already: Few countries have guidelines for the assessment of the likelihood of natural conception to determine access to publicly funded ART. In the Netherlands and New-Zealand, couples with unexplained infertility who have a good prognosis for natural conception are encouraged to delay starting ART. However, the cost-effectiveness of this prognosis-tailored treatment strategy has not been determined. Study design, size, duration: We studied couples with unexplained infertility to compare a prognosis-tailored strategy to care-as-usual. In the prognosis-tailored strategy, couples were assessed using Hunault's prediction model. In good-prognosis couples (12-months natural conception >40%), outcomes without ART were modelled by censoring observations after start of ART. We then assumed that poor-prognosis couples (<40% natural conception) were treated, while good-prognosis couples delayed the start of treatment for 12 months. Data for the care-as-usual model were based on real observations. Participants/materials, setting, methods: We studied 272 couples with unexplained infertility. Costs of in vitro fertilisation (IVF) and intra-uterine insemination (IUI) were calculated based on the out-of-pocket costs and Australian Medicare costs. In a cost-effectiveness model, we compared costs and effects of both strategies. Main results and the role of chance: The prognostic model classified 272 couples with unexplained infertility as favourable (N = 107 (39.3%) or unfavourable prognosis (N = 165 (60.7%)) for natural conception. In the prognosis-tailored strategy, the cumulative live-birth rate was 71.1% (95% CI 64.7% - 76.4%) while the number of ART cycles was 393 (353 IVF; 40 IUI). In care-as-usual strategy, the cumulative conception rate leading to live-birth for the cohort of 272 couples, who underwent a total of 398 IVF cycles and 48 IUI cycles, was 72.1% (95% CI 65.7% - 77.4%). Mean time to conception leading to live birth was 388 days in the prognosis-tailored strategy and 419 days in the care-as-usual strategy. This translated for the 272 couples into potential savings of 45 IVF cycles and eight IUI cycles, which cost a total of AUD 125, 817 for out-of-pocket and AUD 264, 497 for Australian Medicare. The average cost savings per couple was AUD 1, 435 (out-of-pocket AUD 463 per couple and Australian Medicare AUD 962 per couple). The incremental cost-effectiveness ratio, which was calculated as the total costs per additional live-births, was AUD 143, 497 per additional live birth. Limitations, reasons for caution: This study was limited to couples at a single IVF clinic. The modelling was also based on several key assumptions, particularly the number of fresh and frozen embryo transfer cycles for each couple. Wider implications of the findings: Our results show that in couples with unexplained infertility the use of a prognostic model guiding the start of an IVF-treatment reduces costs without compromising live birth rates. Trial registration number: Not applicable